Serological Analysis of Pulmonary and Extra Pulmonary Tuberculosis With Elisa for Anti A60 IgA - Syed Owais Ahmed , Syed Owais Ahmed; Syed Saud Hasan , Syed Saud Hasan; Muhammad Yousuf Salat, Muhammad Yousuf Salat; AftabTurabi, AftabTurabi; Saleem Ahmad Kharal, Saleem Ahmad Kharal; Noshaba Rahat , Noshaba Rahat; Bilquis Begum , Bilquis Begum (Journal of Rawalpindi Medical College, 2007)
Background: Demonstration and evaluation of anti tuberculous IgA antibodies for rapid diagnosis of both pulmonary and extra pulmonary tuberculosis. Method: ELISA assay based on mycobacterial antigen A60 (Anda Biologicals, France) was used on the sera obtained from 69 cases of tuberculosis and 136 controls in the population of Karachi, Pakistan. Result: Of 136 controls only 7.3% were positive for IgA. A very good serological response was observed in cases with sputum positive active pulmonary tuberculosis, depicting a positivity of 83.3% for IgA antibodies. Relatively low sero positivity was seen in cases of sputum negative active pulmonary tuberculosis compared to those of sputum active pulmonary tuberculosis. A low positivity of 26.3% for IgA was observed in cases of extra pulmonary tuberculosis. In cases of healed tuberculosis 25% were found positive for IgA. Considering all the cases of active tuberculosis and the controls the global sensitivity of 58.4% and specificity of 92.7% were obtained when IgA antibodies were taken into account. Conclusion: The estimation of anti tuberculosis antibody IgA against A60 for the rapid diagnosis is clearly demonstrated and therefore recommended